تنوّع استجابات الجمهور في مواقع تقييم الكتب )قودريدز وأبجد أنموذجا( - صيته العذبة (Université de M'sila, 2019)
تركز هذه الورقة البحثية على تنوع الاستجابات بين متصفحي مواقع مراجعة الكتب على الشبكة العنكبوتية، الروايات تحديدا، التي شملت كثيرا من الجوانب المختلفة، منها ما يخص سياقات الروايات المتعددة الثقافي منها والاجتماعي والسياس ي والديني، ومنها ما يخص الشخصيات، ومنها ما يخص اللغة، ومنها ما يخص السرد والحبكة، ومنها ما يخص جوانب خاصة في رواية بعينها. وكل هذه الاستجابات ظهر فيها مرونة مواقع الشبكة وانفتاحها وقدرتها على التشعب، ونقل الاستجابات إلى مراحل أكثر تعمقا وانتشارا، كما أن الاختفاء خلف الأجهزة ربما أتاح مساحة أوسع من الحرية للتعبير وإبداء الرأي. ودراسة هذه الاستجابات كان عبر اختيار نماذج ممثلة لأنماط هذه الاستجابات، هذه النماذج هي : "ساق البامبو" لسعود السنعوس ي في موقع قودريدز، و "أولاد حارتنا" لنجيب محفوظ في موقع أبجد. Abstract: This research paper focuses on the variety of responses among those who peruse the checking books websites on the internet, especially novels. It includes many different aspects, some of them include the contexts of several novels whether they are cultural, social, political or religious novels. Some of them are related to characters, language, narration, plot and others are related to some aspect of a certain novel. All these responses showed the flexibility of the websites, their openness and ability to be divided into hyperlinks and the transfer of responses to deeper and wide spread stages. Also using computers gave more freedom to express and show opinions. Studying these responses was carried out through choosing examples representing these responses such as: "Bamboo Trunk" by Saoud Al Sanoussi on Goodreads website and "The Children of our Lane" by Naguib Mahfouz on Abjad website.
Keywords: استجابات الجمهور، قودريدز، أبجد، ساق البامبو، أولاد حارتنا.Responses of the audience, Goodreads, Abjad, Bamboo Trunk, the Children of our Lane